2017
DOI: 10.5210/ojphi.v9i1.7582
|View full text |Cite
|
Sign up to set email alerts
|

Soda Pop: A Time-Series Clustering, Alarming and Disease Forecasting Application

Abstract: ObjectiveTo introduce Soda Pop, an R/Shiny application designed to be adisease agnostic time-series clustering, alarming, and forecastingtool to assist in disease surveillance “triage, analysis and reporting”workflows within the Biosurveillance Ecosystem (BSVE) [1]. In thisposter, we highlight the new capabilities that are brought to the BSVEby Soda Pop with an emphasis on the impact of metholodogicaldecisions.IntroductionThe Biosurveillance Ecosystem (BSVE) is a biological andchemical threat surveillance syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…From theoretical standpoint, forecasting methods are provided with time series data from previous stages of an outbreak and predicts surveillance attributes of a disease such as the confirmed cases in future. In order to do so, there have been several statistical methods (Reis and Mandl, 2003; Rounds et al, 2017; Zeger et al, 2006; Zhang et al, 2014) suggested by literature. Accordingly, there have been several attempts by professional bodies.…”
Section: Introductionmentioning
confidence: 99%
“…From theoretical standpoint, forecasting methods are provided with time series data from previous stages of an outbreak and predicts surveillance attributes of a disease such as the confirmed cases in future. In order to do so, there have been several statistical methods (Reis and Mandl, 2003; Rounds et al, 2017; Zeger et al, 2006; Zhang et al, 2014) suggested by literature. Accordingly, there have been several attempts by professional bodies.…”
Section: Introductionmentioning
confidence: 99%